Electronic Word of Mouth and Purchase Intention among Urban Consumers: The Mediating Roles of Brand Image and Brand Trust in the Premium Skincare Market - Aisyah Bunga Chaidir; Edi Purwanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat UPJ, 2026)
The rapid growth of digital communication has transformed consumer decision-making processes, particularly through the increasing influence of electronic word of mouth (eWOM). Online reviews and consumer-generated content have become critical sources of information that shape brand perceptions and purchasing behavior in digital marketplaces. This study aims to examine the influence of electronic word of mouth on purchase intention through the mediating roles of brand image and brand trust in the premium skincare market. Drawing on the Stimulus–Organism–Response (S-O-R) framework, eWOM is conceptualized as the external stimulus, brand image and brand trust represent internal psychological responses, and purchase intention represents the behavioral outcome. Data were collected from 155 respondents who were familiar with SK-II skincare products and had been exposed to online reviews related to the brand. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that electronic word of mouth significantly influences purchase intention, brand image, and brand trust. Brand trust also has a significant positive effect on purchase intention, while brand image does not significantly influence purchase intention. Furthermore, brand trust plays a stronger mediating role than brand image in the relationship between eWOM and purchase intention. These findings highlight the importance